Pengungkapan ESG, Efisiensi Biaya dan Ukuran Perusahaan: Dinamika Nilai Perusahaan Sektor Energi Periode 2022-2024 - Tasya Amelia Veronica; Riyan Harbi Valdiansyah (Politeknik Ganesha Medan, 2026)
This study investigates the influence of Environmental, Social, and Governance (ESG) disclosure and cost efficiency on firm value in the Indonesian energy sector, with firm size as a moderating variable. The sample consists of energy companies listed on the Indonesia Stock Exchange during the 2022–2024 period. Data were collected from annual reports and sustainability disclosures, then analyzed using Moderated Regression Analysis (MRA) to capture both direct relationships and moderating effects. The findings reveal that ESG, whether treated as a composite indicator or separated into its components, does not exert a consistent impact on firm value. In contrast, cost efficiency shows a strong and positive effect across all models, highlighting its role as the primary driver of firm valuation. Firm size does not moderate the relationship between ESG and firm value, but it significantly weakens the positive effect of cost efficiency, reflecting the operational complexities faced by larger firms. Sensitivity tests using the Price to Earnings Ratio (PER) confirm that ESG has no significant effect, while cost efficiency consistently enhances firm value. Future research should broaden the sectoral scope, extend the observation period, and incorporate ESG scores from independent rating agencies to strengthen empirical validity and theoretical contributions.